Das ruas às Redes: disputa de narrativas e de memória sobre as ocupações universitárias de 2016 no Ceará em tempos de mediação algorítmica. - Macêdo Júnior, Daniel Paiva de (2020)
The university occupations that occurred in 2016, in Brazil, are inscribed in history as the greatest exponent - until then - of civil resistance and seizure of public spaces in front of the political platform of budget reduction for Education, Health and social investments presented by the Presidency of the Republic that year. If actions like these are evoked with the intention of pressuring visibility of the political agenda, as proposed by Marcuse (1999), they constitute, therefore, a marginal intervention and oriented in communication processes. With attention to the experiences of Ceará and checking that Facebook pages were the main means for the development of communication tactics oriented to the public space, we analyzed six pages produced in the period regarding student incidents at the Federal University of Ceará (@greveestudantilUFC), Federal University of Cariri (@ocupaufca), Universidade Regional do Cariri (@ ocupurca2016), Federal University of Integration of Lusofonia Afrobrasileira (@ocupaunilab) and Federal Institute of Ceará (@ocupaifce and @ocupartes) delimited in 897 publications extracted and systematized via Netvizz. This amount was analyzed in two ways: on the one hand, observing the dynamics of construction of meanings and version of facts that occurred in the occupations in the light of the observations in Content Analysis, according to guidelines by Bardin (2011) in view of the context of dispute of narratives and production of social memory; on the other hand, with a broad look at sociotechnical contexts, changes in the platform and the engineering powers that convene virtual experience, we identified and discussed the social networks resulting from the interaction on the platform, considering those proposed by Recuero et al (2015) and performance of the pages in this ambience. Based on the results and indicators, we established discussions and theoretical propositions around the issues of production and dispute of social memory in the context of algorithmic mediation - with attention to this relationship between ambience and social movements. Keywords: Social Memory. Algorithmic Mediation. Facebook. University Occupations.